Redescubrir la finalidad natural : Robert Spaemann y Tomás de Aquino - Clavell, Lluís (Sapientia, 2014)
On the occasion of the autobiography of Robert Spaemann published in 2012, this paper examines the reading Spaemann makes of the teleology in the doctrine of St. Thomas Aquinas, especially in his work «Natürliche Ziele» (2005) second edition of the version of 1981. In the first part the paper studies the history of teleology in philosophical thought and scientific discussed in «Natural Ends». The intrinsic teleology in the nature of beings is known with increasing depth thanks to Plato, Aristotle, Stoicism and Christian tradition. These contributions are integrated into a unitary structure teleological by Aquinas. Afterwads happens an «inversion» of teleology centered in the self-conservation and a consideration of ends as something external to reality. With evolutionary theory arises the teleonomy limited to the rules of dynamism, suppressing the ends. However, scientists do not reach to eliminate the words «to» or «for» in their language. In that way we can proceed to a rediscovery of natural ends. In the second part, the essay sees how Thomas Aquinas brings knowledge of the teleology beyond Aristotle, because it refers to a creative intelligence. Teleology implies a theology, although is not entirely clear if it is a philosophical or a Christian theology. Spaemann has an ontological proposition of persuasive kind, but at times he feels difficult to overcome in the theoretical level those who sustain a teleonomy.